PENATALAKSANAAN PERAWATAN LUKA DENGAN MODERN DRESSING METCOVAZIN PADA PASIEN LUKA KAKI DIABETIK GRADE III DI WILAYAH KERJA PUSKESMAS BONTOMARANNU GOWA - Cici Anggraeni Cahyati; Nur Wahyuni Munir; Nurwahidah; Suhermi (Jurnal Kesehatan, 2025)
Diabetic foot ulcers are common complications of uncontrolled diabetes mellitus caused by neuropathy, ischemia, and infection. These wounds are often chronic and difficult to heal, requiring an effective wound care approach. This study aims to describe the application of wound care using modern Metcovazin dressing in a patient with a grade III diabetic foot ulcer. This research employed a case study involving one patient (Mrs. R) treated at the Bontomarannu Primary Health Center. The intervention included modern wound care techniques such as wound cleansing, debridement, PHMB application, ozone therapy, and Metcovazin dressing. Findings showed improvement from the first to the second visit, with a reduction in serous exudate from 20% to 15% and an increase in epithelialization from 70% to 85%. These results support Metcovazin dressing as an effective modern dressing method to enhance diabetic ulcer healing.